2010
DOI: 10.1089/pho.2009.2559
|View full text |Cite
|
Sign up to set email alerts
|

Root Surface Biomodification with Nd:YAG Laser for the Treatment of Gingival Recession with Subepithelial Connective Tissue Grafts

Abstract: Background=Aim: Root surface biomodification has been used to treat gingival recession and periodontitis. The principle for this procedure is that removing the smear layer from the root surfaces exposes collagen fibers, which leads to improved healing. Clinical studies generally have failed to find any improvement in clinical parameters when using such procedures, however. The aim of this study was to evaluate and compare the outcome of gingival recession therapy using the subepithelial connective tissue graft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
31
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 45 publications
(110 reference statements)
0
31
1
Order By: Relevance
“…Considering the use of RMA, there is clear support from the literature on the lack of additional benefits provided by the use of chemical agents (i.e., citric acid, EDTA, or tetracycline hydrochloride solution) 4‐7,9,28 or biomodification therapies (i.e., Er:YAG 61 or Nd:YAG lasers 60 ). In general terms, such agents and therapies did not lead to any detrimental effect on the expected final clinical outcomes, and they were not able to improve the results of treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the use of RMA, there is clear support from the literature on the lack of additional benefits provided by the use of chemical agents (i.e., citric acid, EDTA, or tetracycline hydrochloride solution) 4‐7,9,28 or biomodification therapies (i.e., Er:YAG 61 or Nd:YAG lasers 60 ). In general terms, such agents and therapies did not lead to any detrimental effect on the expected final clinical outcomes, and they were not able to improve the results of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 101 articles 30‐131 with 94 RCTs potentially eligible for inclusion into the pooled estimates were identified in the base of evidence, and their main characteristics (i.e., number and age of participants, interventions, follow‐up period, number of sites exhibiting CRC, MRC [percentage], use of RMAs, randomization, allocation concealment, masking of examiners, completeness of the follow‐up period, and risk of bias) are depicted in Table 2 30‐131 . Seven studies were reported in two articles each, and their data were reported under one study name 37,38,57,58,65,66,83,84,90,91,110,111,115,116 …”
Section: Summary Of What Other Srs Have Evaluatedmentioning
confidence: 99%
“…On the other hand, no published data are available concerning the clinical outcomes after root conditioning with Nd:YAG laser for the treatment of intrabony defects with EMP. Previous clinical studies demonstrated that lasers are an effective tool in the field of root conditioning to improve the outcome of regenerative periodontal therapies by favoring the attachment of the regenerated periodontal structures 26‐38 . Among these lasers, the Nd:YAG laser has been reported to remove the smear layer, uncovering dentinal tubules and exposing collagen fibers on root surfaces 31,32 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the exposure of dentinal collagen matrix may also be favorable for retention of biologically active substances, such as EMP 14 . In addition to chemical conditioning, the applicability of different laser systems, such as the CO 2 , the neodymium‐doped:yttrium‐aluminum‐garnet (Nd:YAG), the diode, and the erbium:yttrium‐aluminum‐garnet (Er:YAG), in the removal of the smear layer has been demonstrated 26‐38 . Among these lasers, both the Er:YAG 35 and the 588‐nm diode 39 have been tested for the treatment of intrabony defects with EMP.…”
mentioning
confidence: 99%
See 1 more Smart Citation